THE NEXUS OF ARTIFICIAL INTELLIGENCE, BLOCKCHAIN TECHNOLOGY, AND HUMAN CAPITAL IN DIGITAL MARKETING STRATEGY: AN EXPLORATORY STUDY ON THEINTEGRATION, ETHICAL IMPLICATIONS, AND FUTURE PROSPECTS - Kardi Kardi; Hemi Pamuraharjo, Nawang Kalbuana, Benny Kurnianto (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
In the rapidly evolving digital marketing landscape, the convergence of artificial intelligence (AI), blockchain technology, and human capital management (HCM) is reshaping the strategies that drive businesses forward. This exploratory study delves into the intricate integration of these technologies and their profound implications for digital marketing. Our research uncovers the transformative potential of AI and blockchain in digital marketing. AI's capacity to automate and optimize marketing processes and blockchain's promise of enhanced data security and transparency offer businesses unprecedented tools for customer engagement and operational efficiency. However, this integration raises complex ethical concerns. Balancing the power of AI with responsible data handling and the immutable nature of blockchain with data privacy becomes paramount. HR professionals are pivotal in addressing these challenges as they guide the development of AI-related competencies within the workforce and foster a culture of ethical AI and blockchain use. The study envisions a future marked by even more sophisticated AI-driven marketing strategies and blockchain's disruptive impact on digital advertising. To harness these opportunities, organizations must invest in upskilling their workforce and consider the creation of hybrid job roles blending technical and creative skills. This research contributes valuable insights into the digital marketing landscape, offering guidance on navigating the evolving technological frontier while adhering to ethical principles.